Two new species of Oxytrechus Jeannel, 1927 from Ecuador (Coleoptera, Carabidae) - Giachino, Pier Mauro; Allegro, Gianni; Baviera, Cosimo (Zootaxa, 2014)
Two new species of Oxytrechus Jeannel 1927 are described from the páramos of the Ecuadorian Andes in Pichincha province (Ecuador: Northern Sierra): O. osellai n. sp. from Cangahua at 3375 m a.s.l. and O. belloi n. sp. from Paso de la Virgen at 3515 m a.s.l.